THE ROLE OF PROJECT MANAGEMENT IN THE CREATION AND DEVELOPMENT OF THE TERRITORY’S BRAND - R. Andreeva; O. Sinyaeva (Вестник университета, 2017)
In this article the concept of territory branding is disclosed, the role of events in the development of the territory’s brand is explored, the method of project management is considered as an effective tool for promoting the territory by the analysis of formation and development of well-known brands of territories, such as «Sochi-2014», «EXPO-2017» in Astana, an International sports games (ISG) «Children of Asia in Yakutsk». The experience of the application of PRINCE2 technology (projects in controlled environments version 2) in the creation of the brand ISG «Children of Asia» is studied.